Pengetahuan Awal Mahasiswa pada Mata Kuliah Telaah Kurikulum Biologi - Anggun, Diah Putri; Fernando, Adam (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
An effective understanding of curriculum analysis is crucial for prospective Biology teachers, as it lays the foundation for their future teaching practices. Recognizing the extent of students' foreknowledge in this area is essential to adapting appropriate teaching methods to enhance the student's overall learning experience. This study was conducted in August 2024 to assess the initial knowledge of third-semester Biology Education students at UIN Raden Fatah Palembang regarding the course material. Data were collected and analyzed quantitatively using a closed questionnaire consisting of 10 questions, distributed via Google Forms, with a sample size of 77 students. The primary objective of this research was to evaluate students' prior understanding of the curriculum analysis topics in biology. The results indicated that the average knowledge score among students was only 38.83 with low category, suggesting that many students lacked a solid understanding of the curriculum analysis course material. These findings highlight the need for enhanced instructional strategies and resources to better prepare students for the curriculum analysis course, ultimately improving their comprehension and performance in this essential area of their studies. The novelty of this research is that it reveals learning strategies and policy recommendations that are appropriate to the needs and initial level of understanding of students in taking the Biology Curriculum Review course.